OP0043 A study of overlaping infectious, autoimmune and haematological etiologies in cryoglobulinemia in a tertiary universitary hospital. (1st June 2001) - Ramos-Casals, M; Trejo, O; Garcia-Carrasco, M; Yague, J; De la Red, G; Jimenez, S; Quenard, MI; Cervera, R; Font, J; Ingelmo, M
Abstract : Background: Objectives: To study the main etiological factors associated to cryoglobulinemia in a universitary hospital, to determine the percentage of patients with no evidence of associated disease (?essential? cryoglobulinemia) and to analyse the amount of overlaping between the different etiologies. Methods: We analysed 443 consecutive patients with cryoglobulinemia, who tested positive for circulating cryoglobulins in our Department of Immunology between 1991 and 1999. Of these 443 patients, 258 (58%) were women and 185 (42%) men (mean age 54 years, range 14 to 91). Results: Infectious diseases were detected in 331 (75%) patients, autoimmune diseases in 94 (24%), haematological disease in 33 (7%) and essential cryoglobulinemia in 49 (11%). Patients with autoimmune diseases showed a cryocrit higher than 5% (26%) more frequently compared with those with haematological processes (24%), HCV infection (16%) or essential cryoglobulinemia (2%) (p = 0.003). HCV infection was found in 321 (73%) patients, HBsAg in 15 (3%) and HIV antibodies in 29 (7%). Forty (9%) patients had SJÖGREN'S syndrome (SS), 30 (7%) systemic lupus erythematosus (SLE), 7 (2%) periarteritis nodosa and 6 (2%) progressive systemic sclerosis. Finally, 16 (4%) patients had a NHL, 3 chronic lymphocytic leukaemia, 3 multiple myeloma and 2 Hodgking lymphoma. When the overlaping of more than one etiological factor was analysed, we found that most patients with HBsAg or HIV infection were also HCV positive. In addition, we observed a strong overlap between HCV and some autoimmune (50% in SS, 67% in PAN) or haematological (50% of NHL) diseases. Conclusion: HCV infection was the main etiological factor identified, being present in 73% of patients with cryoglobulinemia. Of the systemic autoimmune diseases, SS and SLE were those frequently associated to cryoglobulinemia, and NHL was the most frequent haematological process found. Associated disease was not found in 11% of patients (essential cryoglobulinemia). Finally, we report a strong overlap between certain etiological factors (HCV, SS and NHL).